Bean pod-like Si@dopamine-derived amorphous carbon@N-doped graphene nanosheet scrolls for high performance lithium storage. Issue 28 (29th June 2016) - Sun, Wei; Wan, Liu; Li, Xiaocheng; Zhao, Xinhong; Yan, Xingbin
Abstract : A bean pod-like void-containing Si@DDAC@N-GNS structure has been elaborately designed and synthesized, which demonstrates highly reversible capacity, excellent rate capability and good cycling stability. Abstract : The high theoretical capacity of Si makes it an attractive anode for lithium ion batteries. But the poor cycling performance, caused by the pulverization of electrode materials during cycling, frustrates its practical applications. Inspired by the structure of the bean pod, here we propose a void-containing a Si@dopamine-derived amorphous carbon@N-doped graphene nanosheet scroll (Si@DDAC@N-GNS) architecture, where Si@DDAC nanoparticles (NPs) are uniformly dispersed within the gallery of N-GNSs, leaving large amounts of voids between Si@DDAC NPs. This typical bean pod-like Si@AADC@N-GNS architecture can be synthesized by freeze-drying the mixed suspension of dopamine decorated Si NPs and graphene oxide followed by a thermal annealing process. The developed unique architecture possesses the typical desired features for high performance Si-based anodes, such as efficient pathways to facilitate electron/ion transportation, good structural durability to buffer the volume variation of Si, and an elastic protecting shell layer to block the deposition of the solid–electrolyte interface film on Si. Owing to these advantages, the resulting Si@DDAC@N-GNS electrode delivered a maximum capacity of 2243 mA h g −1 at a current density of 0.3 A g −1, good rate capability (947.8 mA h g −1 at 3 A g −1 ), and good cycling stability (with a capacity retention of 91.5% after 110 cycles at 2 A g −1 ), suggesting excellent electrochemical performance.